Early turbulence and pulsatile flows enhance diodicity of Tesla’s macrofluidic valve - Quynh M. Nguyen (Nature Portfolio, 2021)
Nguyen et al. take a fresh look at Tesla’s concept of an asymmetric fluidic conduit. They show that for alternating flow at high frequencies the device can almost be operated as a diode, enabled by a transition to turbulent-like flow at rather low Reynolds numbers.